Expression profiling of AUXIN RESPONSE FACTOR genes during somatic embryogenesis induction in Arabidopsis - Wójcikowska, Barbara; Gaj, Małgorzata D. (Plant Cell Reports, 2017)
Extensive modulation of numerous ARF transcripts in the embryogenic culture of Arabidopsis indicates a substantial role of auxin signaling in the mechanism of somatic embryogenesis induction.